Análisis de indicadores de gestión para evaluar el funcionamiento policial de las unidades de policía comunitaria en la administración zonal Manuela Sáenz del Distrito Metropolitano de Quito - Endara Barros, Cristian Andrés (2015)
The analysis of performance indicators to evaluate the functioning of the police Community Policing Units UPC in the Zonal Administration Manuela Sáenz in the Metropolitan District of Quito, is a research project that focuses on identifying and analyzing the behavior of community policing front their objectives and proposed processes and behavior and community collaboration regarding police actions developed. For this research laws, regulations, resolutions, ordinances, etc. is analyzed the same that regulate and establish the functioning of community policing and appropriate management indicators are also used for the purpose of these when we analyze ensure the best results